METHODS OF TEACHING THE UZBEK LANGUAGE IN HIGHER EDUCATION - Samiyevna, Yunusova Gulandom; N.T., Gaybullayeva; G.X., Izzatullayeva; Sh.F, To'xtayev (The journal of contemporary issues in business and government, 2021)
In the following article the modern techniques of teaching the Uzbek language in higher education is analysed based on the metadatas. The modern approaches of teaching the Uzbek language in the academic world is considered. The Uzbek language which used as the native and vernacular language in the world by 50 million speakers is. As it was proclaimed in the decree of the president of the Republic of Uzbekistan on May 13, 2016 on the basis of the faculty of Uzbek philology of National University of Uzbekistan and the faculty of Uzbek language and literature at Tashkent State Pedagogical University new university of Uzbek language and literature was established. This university is considered to be the basic higher educational institution for training translators who are expected to turn the masterpieces of the Uzbek classical and modern literature into an intellectual property of the world community, professional development and retraining of professionals in this field, publication of dictionaries and teaching materials in these areas.